Detection of SARS-CoV-2 Specific Antibodies in Saliva Samples - Yu, Siyang; Zhang, Peiyan; Liao, Mingfeng; Zhang, Juanjuan; Luo, Suisui; Zhai, Jinglei; Zhang, Yaxi; Lin, Jingyan; Yuan, Jing; Zhang, Zheng; Wang, Fuxiang; Wei, Lanlan (Frontiers in Immunology, 2022)
Molecular assays on nasopharyngeal swabs act as a confirmatory test in coronavirus disease (COVID-19) diagnosis. However, the technical requirements of nasopharyngeal sampling and molecular assays limit the testing capabilities. Recent studies suggest the use of saliva for the COVID-19 diagnostic test. In this study, 44 patients diagnosed with COVID-19 in The Third People’s Hospital of Shenzhen were enrolled. Saliva and serum specimens were obtained at different time points and the immunoglobulins against SARS-CoV-2 were measured. The results showed that saliva IgA presented a higher COI value than IgG and IgM. In matched saliva and serum samples, all saliva samples presented lower IgG levels than serum samples, and only one saliva sample presented a higher IgM level. The conversion rates of saliva IgA and the detection of viral nucleic acids were analyzed in the first and second weeks after hospitalization. The positive rates increased when combining saliva IgA and viral nucleic acid detection. In conclusion, our results provide evidence that saliva IgA could serve as a useful index for the early diagnosis of COVID-19.